Human Resource Management Practices and Job Performance: A Study of Malaysian Academic Libraries - Mohamad Azmi, Nur Azia Hazida; Ismail, Fadillah; Che Ismail, Siti Afifah; Md Sarwin, Norfauzan (Journal of Technology Management and Business, 2024)
Job performance stands as a critical element in achieving organizational success, directly influencing productivity, efficiency, and overall workplace effectiveness. Within the realm of academic librarianship in Malaysia, job performance plays a pivotal role in delivering top-notch library services, supporting academic initiatives, and cultivating a conducive learning atmosphere. Despite this significance, there exists a noticeable gap in literature addressing job performance specifically within Malaysian academic libraries. This study aims to fill this void by conducting an extensive literature review and empirical research to shed light on the relationship of job performance and propose strategies for enhancing it among academic librarians. The study targets librarians across 20 public university libraries in Malaysia, analyzing primary data from 287 respondents through inferential statistics using the Statistical Package for the Social Sciences (SPSS). In conclusion, the findings relationship traning and development toward librarian’s job performance that contribute to strong positive relationship with value of pearson correlation, r = 0.486. Ultimately, this study offers recommendations aimed at improving the job performance of academic librarians throughout Malaysia.